Maternal Vaccination as an Integral Part of Life-Course Immunization: A Scoping Review of Uptake, Barriers, Facilitators, and Vaccine Hesitancy for Antenatal Vaccination in Ireland - Adeyinka Sanni; Nuha Ibrahim; Dorothea Tilley; Sandra Bontha; Amy McMorrow; Roy K. Philip (Vaccines)
Background: Maternal vaccination is a critical primary preventive approach and an integral part of life-course immunization strategy, influencing the infection-associated morbidity and mortality in pregnant women, foetuses, and young infants. Despite clear guidelines for the administration of vaccines against tetanus, diphtheria, pertussis (Tdap), influenza, and COVID-19 during pregnancy, maternal vaccination rates remain suboptimal in Ireland as per the National Immunisation Office of the Health Service Executive (HSE). Aim: This review explores the prevailing status, uptake factors, and maternal immunization-specific vaccine hesitancy in Ireland. Method: A scoping review was conducted, searching nine electronic databases, including the Irish health research repository Lenus. The search strategy utilised a Population–Concept–Context framework (pregnant women—vaccine uptake/hesitancy—Ireland). Key factors identified and categorised according to the 5A framework: access, affordability, awareness, acceptance, and activation. Results: Searches yielded 2457 articles, and 12 eligible studies were included for review. Influencing factors were identified in each of the 5A dimensions, with the majority relating to acceptance and awareness. Positively associated factors included healthcare provider (HCP) recommendation and knowledge of vaccine safety. Potential antenatal barriers were maternal lack of knowledge of vaccine-preventable illness severity, infection risks, and vaccine safety concerns. A pregnant woman’s primary motivation for antenatal immunization was protection of her infant; however, the reluctance of HCPs to prescribe all recommended antenatal vaccines, inadequate immunization-specific discussion during antenatal consultations, and suboptimal knowledge of pregnancy-specific vaccine safety hampered potential positive influences. The Irish national immunization policy was a facilitator of affordability. Activation can be achieved through public health awareness campaigns and interdisciplinary promotion of maternal vaccination uptake. Conclusions: Maternal vaccination uptake in Ireland remains suboptimal, and a coordinated, targeted approach updating HCP recommendations, enhancing maternal awareness, and highlighting vaccine safety in pregnancy would be required to meet the life-course immunization goals recommended by WHO. By adopting a life-course immunization approach for healthy living, with maternal vaccination as the pivotal central point, vaccination programmes could close immunity gaps at various life stages.